Analysis of match performance of elite soccer players across confederations during the Men`s and Women`s World Cup - Ju, W.; Cost, R.; Oliva-Lozano, J. M. (Science and Medicine in Football, 2025)
This study aimed to benchmark and analyze match performance of elite soccer players from various confederations during the FIFA World Cup Qatar 2022 (Men`s WC) and FIFA Women`s World Cup Australia and New Zealand 2023 (Women`s WC). A total of 128 matches were analyzed using an optical tracking system (n = 1,351 player observations). Players from various national teams were categorized into their respective confederations: Europe (UEFA), South America (CONMEBOL), North/Central America and Caribbean (CONCACAF), Africa (CAF) and Asia and Oceania (AFC/OFC). Generalized Linear Mixed Models and Linear Mixed Models were employed to assess performance differences between confederations. Data revealed that CONMEBOL players in the Men`s WC covered less total distance than UEFA players (p = 0.0396; ES = 0.6). However, no differences were found in high-intensity running and sprinting distances across confederations in both tournaments. UEFA players in both competitions typically demonstrated superior technical/tactical performances. In particular, UEFA players in the Women`s World Cup made more passes, had 7-16% higher pass completion rates and achieved 10-15% greater line break completion rates compared to those from CAF, CONCACAF and AFC/OFC (p < 0.0001 to p = 0.0199, ES = 0.5-1.3). These findings suggest that UEFA players may possess a tactical/technical edge in international competitions. However, caution should be exercised when interpreting data due to high variations within confederations. This is the first comprehensive study describing match performance between confederations during the Men`s and Women`s WC, providing valuable insights into the physical and technical/tactical aspects of elite soccer.